How Combined Exercise and Vitamin D Supplementation Affect Metabolic Syndrome Risk Factors: A Clinical Trial in Menopausal Women - Parivash Najafi Nazar Abadi; Zaher Etemad; Rastegar Hoseini; Fatah moradi (Fasa University of Medical Sciences, 2020)
Background & Objective: Exercise is a well-known strategy to reduce the risk of metabolic syndrome and chronic disease. However, the concurrent effect of aerobic training with vitamin D supplementation on anthropometric indices and lipid profile are somewhat unknown. This study aimed to investigate the effect of aerobic training and vitamin D supplementation (AT+Vit D) on anthropometric indices and lipid profile in postmenopausal women with metabolic syndrome. Materials & Methods: Forty-six postmenopausal women with metabolic syndrome were randomly assigned to four groups: AT+Vit D (n=11), AT (n=12), Vit D (n=12), and control (C; n=11). The training protocol was incrementally conducted for 8 weeks, 20-40 min of training, with 60-75% HRmax, 3 sessions per week. The intervention groups received capsules of 5000 IU vitamin D or placebo. The data were analyzed through paired t-tests and two-way ANOVA analysis of variance and Bonferroni post hoc test with SPSS 24 at the signification level of P<0.05. Results: All three groups (AT+Vit D, AT, Vit D groups) showed a significant decrease in BW, BMI, BFP, WC, TC, TG, LDL, MAP, and glucose and an increase in HDL. Also, the results showed that AT+Vit D group compared with AT, Vit D, and C groups led to significant reductions in BW, MAP and Glucose TC, TG, and LDL and an increase in HDL (P<0.001 for all three variables). Conclusions: AT+Vit D is more effective in the improvement of lipid profile in patients with NAFLD than AT or Vit D alone.